ANALISIS KESANTUNAN BERBAHASA DALAM ACARA DEBAT CALON PRESIDEN 2024 DI KOLOM KOMENTAR YOUTUBE KOMPASTV - Huda, Muhammad Binur; Setiawan, Kodrat Eko Putro; Ramadhani, Nur Layly Shari (UNIVERSITAS PGRI YOGYAKARTA, 2024)
This study aims to describe and explain the form of adherence to the principles of language politeness found in the comments column of the 2024 presidential candidate debate event on youtube kompastv. This research uses descriptive qualitative research method. The data in this study were obtained from the comments of netizens taken randomly at the first and fifth debates of the 2024 presidential candidates on youtube kompastv. This research uses working tools in the form of data cards and indicators of language politeness principles. The data collection techniques used are listening and note-taking techniques. The data analysis technique used an interactive analysis model. The results of this study found 21 data that included the depth of violation of the principles of language politeness. The amount of data found on the maxim of wisdom amounted to 4 data; the maxim of generosity amounted to 3 data; the maxim of praise amounted to 5 data; the maxim of humility amounted to 2 data; the maxim of sympathy amounted to 4 data; and the maxim of agreement amounted to 3 data. Violation of the principle of language politeness in this study is mostly found in the maxim of praise.